Istinto di morte e conoscenza: due interviste a Massimo Fagioli - Fagioli, Massimo; Palombelli, Barbara; Ubaldi, Daniela (Il sogno della farfalla, 2010)
The release of a new edition of Death Instinct and knowledge, the first edition with the publishers L’Asino d’oro, has triggered off great interest for the work of Massimo Fagioli which has been expressed through a number of public presentations as well as in numerous articles, services and interviews featured on newspapers tv and radio. We are now publishing the transcripts of the interviews that were broadcast respectively on Radiodue Rai and on the private radio station Radio Città Futura on the 7th and 9th April 2010. Both interviews confront the theme of cultural and social changes that had characterized those decades which separate us from the appearance of the first edition, in the early 70s; the former, conducted by Barbara Palombelli, explores in particular the topics related to drug-addiction and youth problems, while the latter, conducted by Daniela Ubaldi, touches on the question of political repercussions of the epistemological revolution ushered in by Death instinct and knowledge.